Squamous cell carcinoma of the hard palate in a 106-year-old woman treated with mold brachytherapy. Issue 1 (January 2017) - Iijima, Yosuke; Hino, Shunsuke; Masuda, Issei; Kawano, Ryutaro; Kaneko, Takahiro; Horie, Norio; Shimoyama, Tetsuo
Abstract: Studies of cancer treatment for centenarians (those who reach 100 years old) have been relatively rare. We present a case of hard palate squamous cell carcinoma in a 106-year-old woman treated using customized mold high-dose-rate brachytherapy, with 4 years of follow-up.